Influence of four dietary oils on selected blood constituents in egg-type chickens - Agboola, Adebisi Favour; Omidiwura, Babatunde Richard; Olurinola, Jeremiah Oluwole (Journal of Agricultural Sciences (Belgrade), 2017)
The enrichment of eggs with polyunsaturated fatty acids (PUFA), particularly with omega-3 fatty acids has attracted the attention of both researchers and the food industry, because these fatty acids are essential for normal body development and play an important role in the prevention of heart diseases. This experiment was conducted to evaluate the effect of four dietary oils on selected blood metabolites in egg-type chickens. One hundred and five (105) Isa Brown laying hens at 34 weeks of age were used and the study lasted for 6 weeks in a completely randomised design. Hens were randomly allotted to seven dietary treatments namely: basal diet (T1), basal diet + 1.5% palm oil (T2), basal diet + 1.5% soybean oil (T3), basal diet + 1.5% sesame seed oil (T4), basal diet + 1.5% fish oil (T5), basal diet + 0.75% soybean oil + 0.75% fish oil (T6) and basal diet + 0.75% sesame seed oil + 0.75% fish oil (T7). The treatments had 5 replicates of 3 hens each. Blood sample (5mls) was collected from the jugular vein of a bird per replicate for serum and haematological parameters. There were no significant differences observed in packed cell volume, haemoglobin, red blood cell, white blood cell, lymphocyte, heterophils and basophils of birds on experimental diets but diets had influence (P
Keywords: Fish oil; Palm oil; Sesame seed oil; Soybean oil; Blood profile; Laying birds